Synthesis and anti-influenza virus activity evaluation of novel andrographolide derivatives - Zou, Chunyang; Men, Jinyu; Qu, Yingjin; Jiang, Chunfeng; Wang, Yao; Chen, Lixia; Yuan, Lei (Medicinal chemistry research, 2022)
In this paper, using AI78-38 , an andrographolide analog with novel skeleton, as the lead compound, we designed and synthesized fifteen amide derivatives at the 17 position of AI78-38 . In the synthesis of key intermediate IM4 , the low yield of the SeO 2 oxidation step impeded the further study. Aiming at improving the yield, White reagent was applied to furnish IM4 by catalyzing the allylic C–H oxidation at the 7, 8, 17 position. It is also firstly reported that White reagent possessed the ability of oxidating the cyclic substrates. Compared with SeO 2 oxidative approach, the modified synthetic method utilized by White reagent increased the yield from 32.0 to 53.6%. The anti-influenza A virus (H3N2) results showed that 4-methoxy derivative 10 offered the greatest inhibitory ability, with an IC 50 value of 90.2 μg/ml, slightly more potent than ribavirin. Furthermore, the drug-likeness and ADMET properties of compound 10 and AI78-38 were evaluated using the Discovery Studio 2.1 software and the online SwissADME. The results showed that compound 10 offered good bioavailability and overcame the disadvantages of the ADMET properties in AI78-38 . Graphical abstract